GELOMBANG ELEKTROMAGNETIK EKAWARNA: REFLEKSINYA PADA, DAN TRANSMISINYA MELINTASI PAPAK DIELEKTRIK - Liek Wilardjo (Techné : Jurnal Ilmiah Elektroteknika, 2012)
Reflection and transmission of monochromatic TEM (transverse electromagnetic) wave incident normally on a lossless dielectric slab will be given in the form of a matrix equation. For a semi-infinite slab, the coefficient of reflection and of transmission will be shown to be the same as those in the respective Fresnel relations.